CCNA Cloud CLDFND 210-451 Official Cert Guide, First Edition - Edgeworth, Brad; Gooley, Jason; Rios, Ramiro Garza (Cisco Press, 2016)
Trust the best selling Official Cert Guide series from Cisco Press to help you learn, prepare, and practice for exam success. They are built with the objective of providing assessment, review, and practice to help ensure you are fully prepared for your certification exam. CCNA Cloud CLDFND 210-451 Official Cert Guide presents you with an organized test preparation routine through the use of proven series elements and techniques. "Do I Know This Already?" quizzes open each chapter and enable you to decide how much time you need to spend on each section. Exam topic lists make referencing easy. Chapter-ending Exam Preparation Tasks help you drill on key concepts you must know thoroughly. Master Cisco CCNA CLDFND 210-451exam topics Assess your knowledge with chapter-opening quizzes Review key concepts with exam preparation tasks Practice with realistic exam questions from the Companion Website CCNA Cloud CLDFND 210-451 Official Cert Guide, focuses specifically on the objectives for the Cisco CCNA CLDFND exam. Leading data center network architect Gustavo A.A. Santana shares preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills. Material is presented in a concise manner, focusing on increasing your understanding and retention of exam topics. The Companion Website contains a powerful Pearson IT Certification Practice Test engine that enables you to focus on individual topic areas or take a complete, timed exam. The assessment engine also tracks your performance and provides feedback on a module-by-module basis, laying out a complete assessment of your knowledge to help you focus your study where it is needed most. Well-regarded for its level of detail, assessment features, comprehensive design scenarios, and challenging review questions and exercises, this official study guide helps you master the concepts and techniques that will enable you to succeed on the exam the first time. The official study guide helps you master all the topics on the CCNA CLDFND exam, including: Cloud characteristics Cloud service models (IaaS, SaaS, PaaS) Cloud deployment (public, private, community, hybrid) Cisco Intercloud Solution Cloud Compute (Cisco UCS) Cloud Networking (DC network architectures, infrastructure virtualization) Cloud Storage basics (provisioning, access, concepts, devices, infrastructures) CCNA Cloud CLDFND 210-451 Official Cert Guide is part of a recommend ...